A zero-energy radiation refrigeration and bacteriostasis synergistic preservation functional nanofiber membrane and a preparation method thereof
Patent Information
- Application Number
- CN202611163526.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]本发明的目的在于克服现有技术存在的上述问题,提供一种零能耗辐射制冷与抑菌协同保鲜功能纳米纤维膜及其制备方法,以解决现有食品保鲜用功能膜材料难以在结构简化条件下兼顾被动降温与抑菌保鲜的问题
(1)本发明通过聚乙烯醇单层静电纺丝纳米纤维网络承载茶树精油-埃洛石纳米管复合物,使被动降温功能和抑菌保鲜功能集成于同一膜层中。茶树精油-埃洛石纳米管复合物随聚乙烯醇纤维同步成型,能够嵌入或固定于纳米纤维内部及表面,使辐射制冷增强相和抑菌缓释组分在膜面范围内分布较均匀,从而使膜材料的降温效果和抑菌效果更易稳定发挥。
Smart Images

Figure CN122879908A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of functional polymer nanofiber membrane materials for food preservation, and in particular to a zero-energy radiation cooling and antibacterial synergistic preservation nanofiber membrane and its preparation method. Background Technology
[0002] Fresh foods such as fruits and vegetables are easily affected by factors such as environmental temperature fluctuations, microbial contamination, and moisture loss during post-harvest storage, transportation, and sales, leading to quality decline, spoilage, and shortened shelf life. As an important protective medium in the circulation of fresh foods, packaging materials have gradually evolved from simple barrier and protection to cutting-edge functions such as temperature control and intelligent antibacterial preservation.
[0003] Radiative cooling materials achieve passive cooling by reflecting sunlight and radiating heat into outer space through atmospheric windows, offering advantages such as requiring no external energy consumption, environmental friendliness, and continuous operation. Existing technologies include methods for preparing radiative cooling films by combining polyvinyl alcohol with inorganic nanoparticles and applying them to the preservation of fruits and vegetables. For example, CN119798893A discloses a radiative cooling film, its preparation method, and its application in the preservation of fruits and vegetables. The film system involves polyvinyl alcohol, glycerol, and inorganic nanoparticles such as nano-titanium dioxide, nano-barium sulfate, or nano-silica. While these materials can improve the passive cooling performance of packaging materials to some extent, their functional design primarily focuses on photothermal regulation, with insufficient attention paid to spoilage caused by microbial contamination.
[0004] Active antibacterial packaging materials inhibit the growth of microorganisms on food surfaces or in the packaging environment by introducing plant essential oils, natural extracts, inorganic antibacterial agents, or other antimicrobial components into the film-forming matrix. Plant essential oils have advantages such as natural origin and broad-spectrum antibacterial activity, but their high volatility can lead to problems such as rapid release and insufficient effective action time when directly added to packaging materials. To improve these issues, existing technologies include encapsulating essential oils in carriers such as halloysite nanotubes before preparing food packaging composite films. For example, CN112679967A discloses a novel active antibacterial food packaging material and its preparation method, which encapsulates essential oils into aminated halloysite nanotubes through physical adsorption, then combines them with other antibacterial components and a zein system, and finally forms an antibacterial food packaging composite film by casting. This type of technology can improve the problem of rapid release of antibacterial agents, but its functional goal is still mainly focused on antibacterial preservation and cannot achieve passive cooling of the packaging microenvironment.
[0005] Therefore, in existing functional film materials for food preservation, passive cooling and antibacterial preservation functions are often achieved separately through different material systems or by constructing different functional layers. While such designs can combine multiple functions to some extent, they typically result in complex material compositions and cumbersome preparation processes. Furthermore, in practical applications, there may still be issues with the cooling and antibacterial effects not being synchronized effectively, leading to unsatisfactory synergistic effects. Therefore, obtaining a food-grade active packaging material with a relatively simplified structure that can simultaneously achieve passive cooling and long-lasting antibacterial preservation remains a pressing technical challenge in this field. Summary of the Invention
[0006] The purpose of this invention is to overcome the above-mentioned problems existing in the prior art and provide a zero-energy radiation cooling and antibacterial synergistic preservation nanofiber membrane and its preparation method, so as to solve the problem that existing functional membrane materials for food preservation are difficult to achieve both passive cooling and antibacterial preservation under the condition of structural simplification.
[0007] To achieve the above objectives, the first aspect of the present invention provides a nanofiber membrane with zero-energy radiation cooling and antibacterial synergistic preservation function. The nanofiber membrane is a single-layer electrospun nanofiber network structure, which includes a polyvinyl alcohol fiber matrix and a tea tree oil-haloite nanotube composite dispersed in the polyvinyl alcohol fiber matrix. The tea tree oil-haloite nanotube composite includes halloysite nanotubes and tea tree oil loaded within the lumen of the halloysite nanotubes. The tea tree oil-haloite nanotube composite is formed synchronously with polyvinyl alcohol fibers and is coated or fixed in the polyvinyl alcohol nanofibers, so that the nanofiber membrane forms a dual sustained-release structure composed of halloysite nanotube lumen loading and polyvinyl alcohol nanofiber coating. Halloysite nanotubes are dispersed in the polyvinyl alcohol fiber matrix to form a micro-nano dispersion interface, and simultaneously serve as a radiation cooling enhancement phase and a tea tree oil slow-release carrier.
[0008] Through this structure, tea tree oil is not simply dispersed freely within polyvinyl alcohol fibers. Instead, it first enters the hollow lumen of halloysite nanotubes and is then encapsulated or immobilized by the polyvinyl alcohol nanofibers along with the halloysite nanotubes. In this way, the release path of tea tree oil is jointly regulated by the confinement of the lumen and the diffusion resistance of the fiber matrix, resulting in a smoother release process and a more sustained antibacterial effect.
[0009] Halloysite nanotubes are not a single filler in this system, but participate simultaneously in photothermal regulation and active material loading within the same fiber network. Their aluminosilicate tubular structure is beneficial for enhancing infrared radiation capability in the 8–13 μm atmospheric window band, and the micro-nano interface formed after dispersion in polyvinyl alcohol fibers can increase the scattering path of incident sunlight inside the fiber membrane, thereby enabling the membrane material to achieve passive cooling capability without relying on external energy consumption.
[0010] Polyvinyl alcohol nanofiber networks, halloysite nanotubes, and tea tree oil are simultaneously formed during electrospinning, placing the cooling and antibacterial functional units within the same monolayer fiber structure. This structure does not simply juxtapose the two functions; rather, it allows the halloysite nanotubes to simultaneously connect the radiative cooling and tea tree oil slow-release processes. Therefore, the membrane material can simultaneously reduce heat accumulation and inhibit microbial growth in fresh food packaging environments, resulting in a more stable overall preservation effect.
[0011] Preferably, the mass ratio of tea tree oil to halloysite nanotubes is 0.8 to 1.2:1.
[0012] Maintaining the mass ratio of tea tree oil to halloysite nanotubes within the aforementioned range facilitates the full entry of tea tree oil into the halloysite nanotube lumen while reducing the residue of free tea tree oil outside the tubes. A suitable lumen loading level ensures the effective content of antibacterial active substances while preventing excessive free oil from adversely affecting the stability of the electrospinning solution and the continuous formation of fibers, thus making it easier for the subsequent fiber membrane to form a uniform and continuous network structure.
[0013] Preferably, the amount of the tea tree oil-haloite nanotube composite is 8% to 16% of the mass of polyvinyl alcohol.
[0014] By controlling the amount of the tea tree oil-halothite nanotube composite within the aforementioned range, a relatively balanced state can be achieved between radiation cooling performance, antibacterial properties, and fiber film-forming stability. When the composite content is too low, the micro / nano scattering interface and tea tree oil loading are insufficient; when the composite content is too high, the number of inorganic tubular particles in the spinning solution increases, easily affecting fiber continuity and dispersion uniformity. The above range enables effective dispersion of halloysite nanotubes in polyvinyl alcohol fibers while maintaining the intact network structure of the nanofiber membrane.
[0015] Preferably, the halloysite nanotube has a diameter of 50–100 nm and a length of 0.5–1.5 μm; hydrogen bonds are formed between the silanol groups on the outer surface of the halloysite nanotube and the hydroxyl groups in the polyvinyl alcohol molecular chain.
[0016] Halloysite nanotubes within the aforementioned size range possess suitable hollow lumens and aspect ratios, facilitating the entry of tea tree oil into the lumens for confined loading and sustained release, while also promoting its uniform dispersion within polyvinyl alcohol fibers. The hydrogen bonding between the silanol groups on the outer surface of the halloysite nanotubes and the hydroxyl groups in the polyvinyl alcohol molecular chains enhances the interfacial stability between the inorganic tubular components and the polymer matrix, reduces the aggregation tendency of the composite during spinning and film formation, and results in a more uniform distribution of functional components within the fiber membrane.
[0017] This interfacial interaction also allows halloysite nanotubes to be more stably embedded or attached to polyvinyl alcohol fibers, enabling them to continuously exert light scattering, infrared radiation, and tea tree oil sustained-release effects within the membrane material. For food preservation packaging materials, the stabilization, uniform dispersion, and efficient loading of functional components can achieve a more uniform cooling and antibacterial synergistic effect, avoiding the problem of insufficient local functionality.
[0018] Preferably, the nanofiber membrane has a porous three-dimensional fiber network structure, the polyvinyl alcohol nanofibers are interwoven to form a porous structure, and the tea tree oil-haloite nanotube composite forms a micro-nano rough structure on the surface of the polyvinyl alcohol nanofibers.
[0019] The porous three-dimensional fiber network structure can increase the air interface and light propagation path inside the membrane material, allowing incident sunlight to undergo multiple scatterings between the fibers, pores, and composite interfaces, thereby improving sunlight reflection capability. The micro-nano rough structure formed by the introduction of tea tree oil-haloite nanotube composite further enriches the fiber surface morphology, making the light scattering interface more complete.
[0020] Meanwhile, the porous fiber network provides a longer path for the slow diffusion of tea tree oil. After being released from the halloysite nanotube lumen, the tea tree oil still needs to migrate gradually through the polyvinyl alcohol fiber matrix and fiber network pores. Therefore, the antibacterial components can act on the packaging microenvironment in a gentler manner, better achieving rapid initial antibacterial action and long-lasting slow antibacterial action, which meets the needs of continuous preservation during the storage of fresh food.
[0021] Preferably, the average solar reflectance of the nanofiber membrane, measured by an ultraviolet-visible-near-infrared spectrophotometer equipped with an integrating sphere in the 300–2500 nm band, is not less than 0.95, and the average infrared emissivity, measured by a Fourier transform infrared spectrometer equipped with an integrating sphere, in the 8–13 μm band, is not less than 0.90.
[0022] The aforementioned solar reflectance and infrared emissivity indicate that this nanofiber membrane can reduce heat absorption at the solar radiation input end and enhance heat radiation outward in the atmospheric window band. The combined effect of these two photothermal behaviors provides the membrane material with a good foundation for passive cooling. For packaging fresh foods such as fruits and vegetables, the reduction in surface temperature of the fiber membrane and the heat accumulation in the packaging microenvironment helps to slow down microbial growth and quality deterioration.
[0023] This performance is not solely due to a single parameter, but rather a result of the porous structure of the polyvinyl alcohol fiber network, the aluminosilicate infrared response characteristics of halloysite nanotubes, and the multiple scattering at the micro-nano dispersion interface. In other words, the material's radiative cooling effect stems from the synergistic interaction between its structure and components, providing a solid foundation for its application as a zero-energy preservation film.
[0024] A method for preparing a nanofiber membrane with synergistic zero-energy radiation cooling and antibacterial preservation functions as described above includes the following steps: S1: Add tea tree essential oil to an ethanol aqueous solution and stir to disperse, to obtain a tea tree essential oil dispersion; S2: Add halloysite nanotubes to the tea tree oil dispersion and stir. Then, vacuum process the suspension containing tea tree oil and halloysite nanotubes to load the tea tree oil into the lumen of the halloysite nanotubes, thus obtaining a tea tree oil-haloysite nanotube loaded system. S3: The tea tree oil-haloite nanotube composite system is centrifuged, the supernatant is discarded, and the precipitate is washed with an ethanol aqueous solution to remove the free tea tree oil on the outer surface of the halloysite nanotubes. After drying, the tea tree oil-haloite nanotube composite is obtained. S4: Polyvinyl alcohol is added to water and heated and stirred to dissolve it, thereby obtaining a polyvinyl alcohol solution. Then, the tea tree oil-haloite nanotube composite is added to the polyvinyl alcohol solution and stirring is continued to obtain an electrospinning precursor solution. S5: Electrospinning the electrospinning precursor liquid to make the tea tree oil-haloite nanotube composite synchronously formed with polyvinyl alcohol fiber, thus obtaining a single-layer electrospinned three-dimensional network nanofiber membrane. S6: The nanofiber membrane is dried to obtain a nanofiber membrane with zero-energy radiation cooling and antibacterial synergistic preservation function.
[0025] This preparation method first loads tea tree oil into halloysite nanotube lumens through stirring and vacuum treatment, then introduces the resulting composite into a polyvinyl alcohol spinning system, and finally constructs a monolayer nanofiber network simultaneously through electrospinning. Vacuum treatment promotes the expulsion of air from the halloysite nanotube lumens, making it easier for tea tree oil to enter. This process sequence ensures that the tea tree oil remains stably loaded within the fiber membrane, rather than being randomly dispersed as free droplets in the spinning system, thus improving the loading stability and controllable release of the antibacterial components from the source.
[0026] In step S3, free tea tree oil on the outer surface of halloysite nanotubes is removed by centrifugation and washing with an ethanol-water solution, ensuring that the subsequent entry into the polyvinyl alcohol solution is primarily composed of the loaded tea tree oil-halosite nanotube complex. This approach helps reduce the impact of free oil on the viscosity, surface tension, and fiber forming state of the spinning solution, making it easier to form continuous fibers during electrospinning and providing a clearer release pathway for the tea tree oil in the final membrane material.
[0027] Electrospinning and simultaneous molding enable the tea tree oil-haloite nanotube composite to be incorporated into the interior of polyvinyl alcohol fibers or fixed to the fiber surface during fiber formation, thereby simultaneously constructing a radiation-cooling interface and an antibacterial sustained-release structure within a single-layer fiber network. While the process is relatively straightforward, the resulting material structure exhibits multi-level interaction pathways, including lumen confinement, fiber coating, micro-nano scattering, and infrared radiation, thus supporting the composite functional performance of the membrane material in food preservation.
[0028] Preferably, in step S1, the volume fraction of ethanol in the ethanol-water solution is 45%–55%, the mass-to-volume ratio of tea tree oil to the ethanol-water solution (50%, v / v) is 1:10, and the stirring and dispersion time is 20–40 min; in step S2, the mass ratio of tea tree oil to halloysite nanotubes is 0.8:1–1.2:1, the stirring time is 2–4 h, the stirring temperature is 20–30 °C, and the vacuum treatment is a double vacuum treatment with a total vacuum treatment time of 10–20 min.
[0029] Controlling the ethanol volume fraction of the aqueous ethanol solution to 45%–55% balances the dispersion of tea tree oil and the subsequent loading of halloysite nanotubes. When the ethanol content is appropriate, tea tree oil is more likely to form a stable dispersion in the system, while the aqueous environment also helps the halloysite nanotubes maintain good wetting and suspension, thus providing more uniform contact conditions for the tea tree oil to enter the tube lumen.
[0030] The ratio of tea tree oil to halloysite nanotubes, stirring time, and temperature all affect the loading process. Maintaining a tea tree oil to halloysite nanotube mass ratio of 0.8:1 to 1.2:1 and stirring at 20–30°C for 2–4 h facilitates the gradual entry of tea tree oil into the halloysite nanotube lumen while reducing the risk of volatilization loss and excessive adsorption on the outer surface. These conditions result in a gentler lumen loading process and facilitate the acquisition of a stable tea tree oil-haloysite nanotube complex.
[0031] Preferably, in step S3, the centrifugal force for centrifugation is 8000–12000 g, and the centrifugation time is 8–15 min; the volume fraction of ethanol in the ethanol aqueous solution used to wash the precipitate is 45%–55%; the drying treatment is vacuum freeze drying, and the vacuum freeze drying time is 18–30 h.
[0032] The centrifugation conditions described above effectively separate the solid-phase complex and liquid-phase components in the tea tree oil-haloite nanotube supported system, allowing unloaded or weakly adsorbed tea tree oil to be removed with the supernatant. Washing the precipitate with a 45%–55% ethanol aqueous solution further reduces the amount of free essential oil residue on the outer surface of the halloysite nanotubes, ensuring that the tea tree oil is primarily retained in the complex in a tubular loaded state.
[0033] Vacuum freeze-drying can remove solvents at lower temperatures, reducing the volatilization loss of tea tree oil during the drying process and also helping to maintain the dispersibility of the halloysite nanotube composite. The tea tree oil-haloysite nanotube composite obtained after this treatment is more suitable for addition to polyvinyl alcohol solution for subsequent spinning, which can reduce the risk of agglomeration and localized oil precipitation, making the structure and function of the final fiber membrane more stable.
[0034] Preferably, in step S4, the polyvinyl alcohol solution contains 8%–12% polyvinyl alcohol by mass, and the polyvinyl alcohol is stirred and dissolved at 70–80°C for 8–14 h; after the tea tree oil-haloite nanotube composite is added, stirring continues for 2–6 h, and the amount of tea tree oil-haloite nanotube composite added is 4%–20% of the mass of polyvinyl alcohol; In step S5, the needle size for electrospinning is 18 to 22, the receiving distance is 10 to 20 cm, the spinning voltage is 10 to 20 kV, the spinning flow rate is 0.2 to 0.8 mL / h, the ambient temperature is 20 to 30℃, and the relative humidity is 35% to 50%.
[0035] The polyvinyl alcohol (PVA) mass fraction was controlled at 8%–12%, and it was thoroughly stirred and dissolved at 70–80°C, which is beneficial for forming a spinning matrix with moderate viscosity and sufficient chain entanglement. The PVA solution in this state can both support the tea tree oil-haloite nanotube composite and be stably stretched into fibers under the action of an electric field, thus providing a basis for the formation of a continuous nanofiber network.
[0036] Adding the tea tree oil-haloite nanotube composite and continuing stirring for 2–6 hours promotes uniform dispersion of the composite in the polyvinyl alcohol solution and ensures sufficient contact between the silanol groups on the outer surface of the halloysite nanotubes and the hydroxyl groups of the polyvinyl alcohol molecular chains. This interfacial contact improves the stability of the composite in the spinning system, allowing it to be more uniformly embedded or fixed within the polyvinyl alcohol fibers during fiber forming.
[0037] Controlling the electrospinning needle specifications, receiving distance, voltage, spinning flow rate, temperature, and humidity within the aforementioned ranges facilitates the formation of a stable Taylor cone in the spinning solution and its continuous stretching into fibers. A stable electrospinning process reduces bead-like defects and fiber breakage, allowing the nanofiber membrane to maintain a relatively intact porous network structure. This network structure not only contributes to light scattering and infrared radiation but also provides uniform diffusion channels for the gradual release of tea tree oil, thus enabling a more coordinated performance of passive cooling and antibacterial preservation functions within the same membrane material.
[0038] The present invention, by adopting the above technical solution, has the following beneficial effects: (1) In this invention, a tea tree oil-haloite nanotube composite is supported by a polyvinyl alcohol monolayer electrospun nanofiber network, thereby integrating passive cooling and antibacterial preservation functions into the same membrane layer. The tea tree oil-haloite nanotube composite is formed synchronously with the polyvinyl alcohol fibers, and can be embedded or fixed inside and on the surface of the nanofibers, so that the radiation cooling enhancement phase and the antibacterial slow-release component are more evenly distributed within the membrane surface, thus making it easier for the membrane material to exert its cooling and antibacterial effects more stably.
[0039] (2) In this invention, tea tree oil is loaded into the lumen of halloysite nanotubes and further coated or fixed by polyvinyl alcohol nanofibers to form a sustained-release structure with the combined effect of lumen confinement and fiber coating. During the release process, the tea tree oil is dually regulated by the lumen of halloysite nanotubes and the polyvinyl alcohol fiber matrix, which can reduce the impact of rapid volatilization and short-term concentrated release of free oil, thereby providing a more stable antibacterial and preservation effect.
[0040] (3) In this invention, halloysite nanotubes are dispersed in a polyvinyl alcohol fiber matrix to form a micro-nano dispersion interface. Their aluminosilicate structure is beneficial to enhancing the infrared radiation capability in the atmospheric window band, and the multi-scale interface formed by the fiber network and tubular particles is beneficial to increasing the solar light scattering path. The resulting nanofiber membrane can enhance infrared heat dissipation while reducing solar radiation heat input, and promotes the coordinated effect of passive cooling and continuous antibacterial function through the porous three-dimensional fiber network and micro-nano rough structure.
[0041] (4) The present invention employs a process route of first loading tea tree oil, then removing free tea tree oil from the outer surface, and subsequently adding a polyvinyl alcohol spinning system for electrospinning. This allows the tea tree oil to enter the fiber membrane primarily in a tubular loaded state. This process helps reduce the influence of free oil on the viscosity, surface tension, and continuous fiber formation of the spinning solution, improves the stability and structural integrity of the nanofiber membrane, and has clear process steps, making it suitable for preparing functional packaging materials for food preservation. Attached Figure Description
[0042] Figure 1 SEM images of the nanofiber membranes prepared in Comparative Examples 1, 5, 1, and 6.
[0043] Figure 2 The graph shows the solar reflectance of the nanofiber membranes prepared in Comparative Examples 1, 5, 1, and 6.
[0044] Figure 3 The infrared emissivity curves are for the nanofiber membranes prepared in Comparative Examples 1, 5, 1, and 6.
[0045] Figure 4 The diagram shows the antibacterial effect of the nanofiber membranes prepared in Comparative Examples 1, 3 and 1 against Escherichia coli and Staphylococcus aureus.
[0046] Figure 5 Simulated daytime cooling curves of samples prepared from paper-based materials, polypropylene film, polyethylene terephthalate film, Comparative Example 1, and Example 1. Detailed Implementation
[0047] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0048] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.
[0049] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0050] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0051] The present invention will now be described in detail with reference to specific embodiments, which are intended to understand rather than limit the invention.
[0052] Unless otherwise specified, in the following examples, tea tree oil is a natural plant essential oil derived from the leaves of Melaleuca alternifolia, and is a pale yellow to colorless transparent liquid at room temperature, suitable for constructing antibacterial functions in food packaging materials. Halloysite nanotubes are natural hollow tubular aluminosilicate materials with a diameter of 50–100 nm and a length of 0.5–1.5 μm. Polyvinyl alcohol is water-soluble polyvinyl alcohol with a degree of alcoholysis of 87–89% (mol / mol), suitable for electrospinning films in aqueous solutions.
[0053] Example 1 This embodiment discloses a method for preparing a 12% TTO-HNTs / PVA nanofiber membrane, comprising the following steps: S1: Weigh 2.00 g of tea tree oil and add it to 20.0 mL of 50% ethanol aqueous solution. Stir at 500 rpm for 30 min at 25℃ to obtain tea tree oil dispersion.
[0054] S2: Add 2.00 g halloysite nanotubes to the tea tree oil dispersion, stir at 500 rpm for 2 h at 25 °C, and then perform vacuum treatment twice for 15 min each time to allow the tea tree oil to enter the halloysite nanotube lumen, thus obtaining the tea tree oil-haloysite nanotube loaded system.
[0055] S3: The tea tree oil-haloite nanotube loading system was centrifuged at 10000×g for 10 min, and the supernatant was discarded. 20.0 mL of 50% (v / v) ethanol aqueous solution was added to the precipitate, and the mixture was shaken and dispersed for 2 min. The mixture was then centrifuged again at 10000×g for 10 min, and the supernatant was discarded. The precipitate obtained by centrifugation was placed in a vacuum freeze dryer and dried for 24 h at a cold trap temperature of -50℃ and a chamber pressure not exceeding 30 Pa to obtain the tea tree oil-haloite nanotube composite.
[0056] S4: Weigh 2.00 g of polyvinyl alcohol and add it to 20.0 mL of deionized water. Stir at 500 rpm for 12 h in a 75℃ water bath until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol solution. Add 240 mg of tea tree oil-halothite nanotube composite to the polyvinyl alcohol solution and continue stirring at 500 rpm for 4 h in a 25℃ water bath. Then allow it to stand for 30 min to remove bubbles to obtain the electrospinning precursor solution.
[0057] S5: The electrospinning precursor solution was loaded into a 10 mL syringe and connected to a No. 21 metal needle for electrospinning. The electrospinning voltage was 15 kV, the distance from the needle to the receiving plate was 15 cm, the spinning flow rate was 0.4 mL / h, the ambient temperature was 25℃, and the relative humidity was 40%. During the spinning process, the precursor solution formed a stable Taylor cone under the action of the electric field, and a continuous monolayer nanofiber film was formed on the aluminum foil receiving plate.
[0058] S6: Peel the collected nanofiber membrane from the aluminum foil receiving plate and place it in a dry environment at 25°C and 30% relative humidity for 24 h to obtain a 12% TTO-HNTs / PVA nanofiber membrane.
[0059] Example 2 This embodiment discloses a method for preparing an 8% TTO-HNTs / PVA nanofiber membrane. The difference between this embodiment and Example 1 is that the amount of tea tree oil-halothite nanotube composite added in step S4 is 160 mg, while the remaining raw materials, operating steps, and process parameters are the same as in Example 1, resulting in an 8% TTO-HNTs / PVA nanofiber membrane.
[0060] Example 3 This embodiment discloses a method for preparing a 16% TTO-HNTs / PVA nanofiber membrane. The difference between this embodiment and Example 1 is that the amount of tea tree oil-haloite nanotube composite added in step S4 is 320 mg, while the remaining raw materials, operating steps, and process parameters are the same as in Example 1, resulting in a 16% TTO-HNTs / PVA nanofiber membrane.
[0061] Example 4 This embodiment discloses a method for preparing a TTO-HNTs / PVA nanofiber membrane with a tea tree oil to halloysite nanotube mass ratio of 0.8:1. The difference between this embodiment and Example 1 is that in step S1, the amount of tea tree oil added is 1.60 g; in step S2, the amount of halloysite nanotubes added is 2.00 g; and the mass ratio of tea tree oil to halloysite nanotubes is 0.8:1. In step S4, the amount of tea tree oil-haloysite nanotube composite added is 240 mg. All other raw materials, operating steps, and process parameters are the same as in Example 1, resulting in a TTO-HNTs / PVA nanofiber membrane with a TTO:HNTs mass ratio of 0.8:1.
[0062] Example 5 This embodiment discloses a method for preparing a TTO-HNTs / PVA nanofiber membrane with a tea tree oil to halloysite nanotube mass ratio of 1.2:1. The difference between this embodiment and Example 1 is that the amount of tea tree oil added in step S1 is 2.40 g, the amount of halloysite nanotubes added in step S2 is 2.00 g, and the mass ratio of tea tree oil to halloysite nanotubes is 1.2:1; the amount of tea tree oil-haloysite nanotube composite added in step S4 is 240 mg. All other raw materials, operating steps, and process parameters are the same as in Example 1, resulting in a TTO-HNTs / PVA nanofiber membrane with a TTO:HNTs mass ratio of 1.2:1.
[0063] Comparative Example 1 This comparative example discloses a method for preparing a PVA nanofiber membrane. The difference between this comparative example and Example 1 is that steps S1-S3 are omitted, and the tea tree oil-halothite nanotube composite is not added. 2.00 g of polyvinyl alcohol is weighed and added to 20.0 mL of deionized water. The mixture is stirred at 500 rpm for 12 h in a 75°C water bath to obtain a PVA electrospinning precursor solution. The electrospinning and drying conditions are the same as in Example 1, resulting in a PVA nanofiber membrane.
[0064] Comparative Example 2 This comparative example discloses a method for preparing a TTO / PVA nanofiber membrane. The difference between this comparative example and Example 1 is that halloysite nanotubes are not added, nor is tea tree oil-haloysite nanotube preloading performed. Specifically, 120 mg of tea tree oil was weighed and added to 1.2 mL of a 50% (v / v) ethanol aqueous solution. The mixture was stirred at 500 rpm for 30 min at 25°C to obtain a tea tree oil pre-dispersion. 2.00 g of polyvinyl alcohol was weighed and added to 18.8 mL of deionized water. The mixture was stirred at 500 rpm for 12 h at 75°C in a water bath to completely dissolve the polyvinyl alcohol. The tea tree oil pre-dispersion was slowly added dropwise to the polyvinyl alcohol solution, and the mixture was stirred at 500 rpm for 4 h at 25°C. After standing for 30 min to remove bubbles, a TTO / PVA electrospinning precursor solution was obtained. The electrospinning and drying conditions were the same as in Example 1, resulting in a TTO / PVA nanofiber membrane. The 120 mg tea tree oil was calculated based on the theoretical feed ratio of 240 mg tea tree oil-haloite nanotube composite in Example 1.
[0065] Comparative Example 3 This comparative example discloses a method for preparing an HNTs / PVA nanofiber membrane. The difference between this comparative example and Example 1 is that tea tree oil is not added, nor is the tea tree oil-haloite nanotube pre-loading performed. Specifically, 2.00 g of polyvinyl alcohol is weighed and added to 18.8 mL of deionized water. The mixture is stirred at 500 rpm for 12 h at 75°C in a water bath until the polyvinyl alcohol is completely dissolved. 120 mg of halloysite nanotubes are added to the polyvinyl alcohol solution and stirred at 500 rpm for 4 h at 25°C. The mixture is then allowed to stand for 30 min to remove bubbles, yielding an HNTs / PVA electrospinning precursor solution. The electrospinning and drying conditions are the same as in Example 1, resulting in the HNTs / PVA nanofiber membrane. The 120 mg of halloysite nanotubes is calculated based on the theoretical feed ratio of 240 mg of the tea tree oil-haloite nanotube composite in Example 1.
[0066] Comparative Example 4 This comparative example discloses a method for preparing an unloaded TTO-HNTs / PVA nanofiber membrane. The difference between this comparative example and Example 1 is that the tea tree oil and halloysite nanotubes were not pre-treated with stirring-vacuum assisted tube loading, centrifugation washing, and vacuum freeze-drying, but were directly added to the polyvinyl alcohol solution.
[0067] The specific operation is as follows: 120 mg of tea tree oil and 120 mg of halloysite nanotubes were weighed and added to 1.2 mL of 50% ethanol aqueous solution. The mixture was stirred at 500 rpm for 30 min at 25°C to obtain a dispersion of unloaded TTO-HNTs. 2.00 g of polyvinyl alcohol was weighed and added to 18.8 mL of deionized water. The mixture was stirred at 500 rpm for 12 h at 75°C to completely dissolve the polyvinyl alcohol. The unloaded TTO-HNTs dispersion was slowly added to the polyvinyl alcohol solution. The mixture was stirred at 500 rpm for 4 h at 25°C and allowed to stand for 30 min to remove bubbles, resulting in a precursor solution for electrospinning of unloaded TTO-HNTs / PVA. The electrospinning and drying conditions were the same as in Example 1 to obtain an unloaded TTO-HNTs / PVA nanofiber membrane. The 120 mg tea tree oil and 120 mg halloysite nanotubes were calculated according to the theoretical feeding ratio of 240 mg tea tree oil-haloysite nanotube composite in Example 1.
[0068] Comparative Example 5 This comparative example discloses a method for preparing a 4% TTO-HNTs / PVA nanofiber membrane. The difference between this comparative example and Example 1 is that the amount of tea tree oil-halothite nanotube composite added in step S4 is 80 mg, while the remaining raw materials, operating steps, and process parameters are the same as in Example 1, resulting in a 4% TTO-HNTs / PVA nanofiber membrane.
[0069] Comparative Example 6 This comparative example discloses a method for preparing a 20% TTO-HNTs / PVA nanofiber membrane. The difference between this comparative example and Example 1 is that the amount of tea tree oil-halothite nanotube composite added in step S4 is 400 mg, while the remaining raw materials, operating steps, and process parameters are the same as in Example 1, resulting in a 20% TTO-HNTs / PVA nanofiber membrane.
[0070] Performance testing To verify the microstructure, radiative cooling performance, antibacterial performance, tea tree oil release performance, and simulated cooling effect of the nanofiber membrane of the present invention, the samples obtained from the examples and comparative examples were tested as follows. The test samples included Examples 1 to 3 and Comparative Examples 1 to 6, wherein Example 1 was a 12% TTO-HNTs / PVA nanofiber membrane, Comparative Example 1 was a PVA nanofiber membrane, Comparative Example 2 was a TTO / PVA nanofiber membrane, Comparative Example 3 was an HNTs / PVA nanofiber membrane, Comparative Example 4 was an unloaded TTO-HNTs / PVA nanofiber membrane, Comparative Example 5 was a 4% TTO-HNTs / PVA nanofiber membrane, and Comparative Example 6 was a 20% TTO-HNTs / PVA nanofiber membrane.
[0071] 1. Microscopic morphological observation The nanofiber membranes obtained from Comparative Example 1, Comparative Example 5, Example 1 and Comparative Example 6 were cut into 5mm×5mm samples, fixed on conductive adhesive, and observed for fiber morphology using a scanning electron microscope after gold sputtering treatment with an accelerating voltage of 5kV. Figure 1 SEM images of nanofiber membranes with different amounts of TTO-HNTs. Figure 1 It can be seen that the PVA nanofiber membrane obtained in Comparative Example 1 exhibits a continuous fiber network structure with a relatively smooth fiber surface. With the addition of the TTO-HNTs composite, a micro-nano rough structure gradually appears on the fiber surface, while the fibers still maintain an interwoven porous network. In the 12% TTO-HNTs / PVA nanofiber membrane obtained in Example 1, the composite is distributed relatively evenly in the fibers, and the fiber continuity is good. In Comparative Example 6, after the TTO-HNTs addition amount was increased to 20%, local particle aggregation and uneven fiber thickness were observed, indicating that an excessively high content of inorganic tubular composite will affect the stability of electrospinning.
[0072] 2. Detection of solar reflectivity and infrared emissivity Each sample was cut into 30 mm × 30 mm film sheets and fixed flat on the sample stage. The reflectance in the 300–2500 nm wavelength band was measured using a UV-Vis-NIR spectrophotometer equipped with an integrating sphere, and the average solar reflectance was calculated using AM1.5 solar spectral weighting. The infrared spectrum in the 2.5–25 μm wavelength band was measured using a Fourier transform infrared spectrometer equipped with an integrating sphere, and the average infrared emissivity in the 8–13 μm atmospheric window band was calculated. Figure 2 Solar reflectance curves of nanofiber membranes with different amounts of TTO-HNTs added. Figure 3 Infrared emissivity curves of nanofiber membranes with different amounts of TTO-HNTs. Figure 2 and Figure 3 It can be seen that after the addition of the TTO-HNTs composite, the nanofiber membrane maintains high reflectivity in the solar radiation band, while exhibiting high infrared emissivity in the 8–13 μm band. The average solar reflectivity of the 12% TTO-HNTs / PVA nanofiber membrane obtained in Example 1 is 0.995, and the average infrared emissivity is 0.941, indicating that the membrane can reduce solar radiation heat input and enhance infrared radiation heat dissipation.
[0073] Table 1. Average solar reflectance and average infrared emissivity of different nanofiber membranes
[0074] As shown in Table 1, in Comparative Example 2, the addition of tea tree oil directly did not significantly improve solar reflectivity and infrared emissivity. In Comparative Example 3, the addition of halloysite nanotubes significantly improved both solar reflectivity and infrared emissivity, indicating that halloysite nanotubes help form a light scattering interface and enhance infrared radiation. Example 1, while maintaining a good fiber structure, introduced a TTO-HNTs complex, resulting in high reflectivity and emissivity. Although Comparative Example 6 had a high complex content, its photothermal performance did not further improve due to localized agglomeration and decreased fiber uniformity.
[0075] 3. Antibacterial performance test Weigh 40 mg of each sample and place them in a 2 mL sterile centrifuge tube. Add 1.0 mL of a 1.0 × 10⁻⁶ solution. 8 CFU / mL *E. coli* suspension was co-cultured at 37°C and 150 rpm for 24 h. The detection method for *Staphylococcus aureus* was the same as for *E. coli*. After incubation, the co-culture solution was serially diluted 10-fold, and 100 μL of each dilution was plated onto nutrient agar plates and incubated at 37°C for 24 h before counting. A bacterial suspension without membrane material was used as a blank control, and the inhibition rate was calculated based on the number of colonies. Figure 4 This image shows the antibacterial effects of different nanofiber membranes. Figure 4 It can be seen that the 12% TTO-HNTs / PVA nanofiber membrane obtained in Example 1 has a significant inhibitory effect on Escherichia coli and Staphylococcus aureus, indicating that tea tree oil can still effectively exert antibacterial activity after being loaded with halloysite nanotubes and entering the PVA nanofiber network.
[0076] Table 2 Antibacterial rates of different nanofiber membranes
[0077] Table 2 shows that Comparative Examples 1 and 3 exhibited weak inhibitory effects against both bacteria, indicating that the PVA matrix and the halloysite nanotubes without tea tree oil loading were not the primary sources of antibacterial activity. Comparative Example 2, with the direct addition of tea tree oil, showed some antibacterial effect, but the tea tree oil was in a relatively free state, resulting in insufficient persistence of subsequent release. Example 1 achieved antibacterial rates of 85.1% against Escherichia coli and 96.0% against Staphylococcus aureus, demonstrating that the tea tree oil loaded into the tube lumen maintained effective antibacterial activity within the PVA nanofiber membrane.
[0078] 4. Tea tree oil release performance test 100 mg of samples from Comparative Examples 2, 4, and 1 were weighed and placed in 50 mL of 50% (v / v) ethanol aqueous solution, and released by shaking at 25 °C and 100 rpm. Samples were taken in 2 mL increments at 1 h, 12 h, 24 h, 72 h, and 168 h, and an equal volume of fresh release medium was added. The absorbance was measured at 298 nm using a UV-Vis spectrophotometer, and the cumulative release rate was calculated based on the tea tree oil standard curve. The test results are shown in Table 3. Table 3 shows that the release process of tea tree oil in the nanofiber membrane obtained in Example 1 is more gradual, indicating that the halloysite nanotube lumen and the PVA fiber matrix can jointly regulate the tea tree oil release pathway.
[0079] Table 3. Cumulative release rate of tea tree oil from different nanofiber membranes
[0080] As shown in Table 3, in Comparative Example 2, tea tree oil was directly dispersed in PVA nanofibers, resulting in rapid initial release, with a cumulative release rate of 79.4% after 24 hours. In Comparative Example 4, tea tree oil and halloysite nanotubes were not pre-loaded, leading to a reduced release rate, but still significant initial release was observed. In Example 1, tea tree oil was first loaded into the lumen of halloysite nanotubes and then entered the PVA nanofiber network with the complex. The cumulative release rate was 39.6% after 24 hours and 72.4% after 168 hours, indicating that lumen confinement and fiber coating can jointly delay the migration of tea tree oil, enabling the continuous release of antibacterial active substances.
[0081] 5. Simulated daytime cooling performance test The sample was cut into 7 cm × 7 cm square films and placed on the surface of an insulated cavity box with a top opening of 5 cm × 5 cm. Xenon lamps were used to simulate solar irradiation at an intensity of 1000 W / m². 2 The test environment temperature was 25.0 ± 0.5℃ and the relative humidity was 45 ± 5%. The sample surface temperature was recorded every 10 minutes during the test, and the irradiation was continuous for 2 hours. Figure 5 Simulated daytime cooling curves for different packaging materials. Figure 5 It can be seen that the surface temperature of the 12% TTO-HNTs / PVA nanofiber membrane obtained in Example 1 was 23.8℃ after 2 hours of simulated sunlight irradiation, which is lower than that of paper-based materials, polypropylene, polyethylene terephthalate and PVA nanofiber membrane, indicating that it has a good passive cooling capability.
[0082] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A nanofiber membrane with zero-energy radiative cooling and antibacterial synergistic preservation function, characterized in that, The nanofiber membrane is a single-layer electrospun nanofiber network structure, which includes a polyvinyl alcohol fiber matrix and a tea tree oil-haloite nanotube composite dispersed in the polyvinyl alcohol fiber matrix. The tea tree oil-haloite nanotube composite includes halloysite nanotubes and tea tree oil loaded within the lumen of the halloysite nanotubes. The tea tree oil-haloite nanotube composite is formed synchronously with polyvinyl alcohol fibers and is coated or fixed in the polyvinyl alcohol nanofibers, so that the nanofiber membrane forms a dual sustained-release structure composed of halloysite nanotube lumen loading and polyvinyl alcohol nanofiber coating. Halloysite nanotubes are dispersed in the polyvinyl alcohol fiber matrix to form a micro-nano dispersion interface, and simultaneously serve as a radiation cooling enhancement phase and a tea tree oil slow-release carrier.
2. The nanofiber membrane with zero-energy radiative cooling and antibacterial synergistic preservation function according to claim 1, characterized in that, The mass ratio of tea tree oil to halloysite nanotubes is 0.8–1.2:
1.
3. The nanofiber membrane with zero-energy radiative cooling and antibacterial synergistic preservation function according to claim 1, characterized in that, The amount of the tea tree oil-haloite nanotube composite used is 8% to 16% of the mass of polyvinyl alcohol.
4. The nanofiber membrane with zero-energy radiative cooling and antibacterial synergistic preservation function according to claim 1, characterized in that, The halloysite nanotubes have a diameter of 50–100 nm and a length of 0.5–1.5 μm; hydrogen bonds are formed between the silanol groups on the outer surface of the halloysite nanotubes and the hydroxyl groups in the polyvinyl alcohol molecular chain.
5. The nanofiber membrane with zero-energy radiative cooling and antibacterial synergistic preservation function according to claim 1, characterized in that, The nanofiber membrane has a porous three-dimensional fiber network structure. The polyvinyl alcohol nanofibers interweave to form a porous structure, and the tea tree oil-haloite nanotube composite forms a micro-nano rough structure on the surface of the polyvinyl alcohol nanofibers.
6. The nanofiber membrane with zero-energy radiative cooling and antibacterial synergistic preservation function according to claim 1, characterized in that, The average solar reflectance of the nanofiber membrane, measured by an ultraviolet-visible-near-infrared spectrophotometer equipped with an integrating sphere in the 300–2500 nm band, is not less than 0.95, and the average infrared emissivity, measured by a Fourier transform infrared spectrometer equipped with an integrating sphere in the 8–13 μm band, is not less than 0.
90.
7. A method for preparing a nanofiber membrane with synergistic preservation function of zero-energy radiation cooling and antibacterial properties as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1: Add tea tree essential oil to an ethanol aqueous solution and stir to disperse, to obtain a tea tree essential oil dispersion; S2: Add halloysite nanotubes to the tea tree oil dispersion and stir. Then, vacuum process the suspension containing tea tree oil and halloysite nanotubes to load the tea tree oil into the lumen of the halloysite nanotubes, thus obtaining a tea tree oil-haloysite nanotube loaded system. S3: The tea tree oil-haloite nanotube composite system is centrifuged, the supernatant is discarded, and the precipitate is washed with an ethanol aqueous solution to remove the free tea tree oil on the outer surface of the halloysite nanotubes. After drying, the tea tree oil-haloite nanotube composite is obtained. S4: Polyvinyl alcohol is added to water and heated and stirred to dissolve it, thereby obtaining a polyvinyl alcohol solution. Then, the tea tree oil-haloite nanotube composite is added to the polyvinyl alcohol solution and stirring is continued to obtain an electrospinning precursor solution. S5: Electrospinning the electrospinning precursor liquid to make the tea tree oil-haloite nanotube composite synchronously formed with polyvinyl alcohol fiber, thus obtaining a single-layer electrospinned three-dimensional network nanofiber membrane. S6: The nanofiber membrane is dried to obtain a nanofiber membrane with zero-energy radiation cooling and antibacterial synergistic preservation function.
8. The method for preparing the nanofiber membrane with zero-energy radiation cooling and antibacterial synergistic preservation function according to claim 7, characterized in that, In step S1, the volume fraction of ethanol in the ethanol-water solution is 45%–55%, the mass-volume ratio of tea tree oil to ethanol-water solution (50%, v / v) is 1:10, and the stirring and dispersion time is 20–40 min; in step S2, the mass ratio of tea tree oil to halloysite nanotubes is 0.8:1–1.2:1, the stirring time is 2–4 h, the stirring temperature is 20–30 °C, and the vacuum treatment is performed twice, with a total vacuum treatment time of 10–20 min.
9. The method for preparing the nanofiber membrane with zero-energy radiation cooling and antibacterial synergistic preservation function according to claim 7, characterized in that, In step S3, the centrifugal force for centrifugation is 8000–12000 g, and the centrifugation time is 8–15 min; the volume fraction of ethanol in the ethanol aqueous solution used to wash the precipitate is 45%–55%; the drying treatment is vacuum freeze drying, and the vacuum freeze drying time is 18–30 h.
10. The method for preparing the nanofiber membrane with zero-energy radiation cooling and antibacterial synergistic preservation function according to claim 7, characterized in that, In step S4, the polyvinyl alcohol solution contains 8%–12% polyvinyl alcohol by mass, and the polyvinyl alcohol is stirred and dissolved at 70–80°C for 8–14 h; after the tea tree oil-haloite nanotube composite is added, stirring continues for 2–6 h, and the amount of tea tree oil-haloite nanotube composite added is 4%–20% of the mass of polyvinyl alcohol; The needle specifications for electrospinning are No. 18 to No. 22, the receiving distance is 10 to 20 cm, the spinning voltage is 10 to 20 kV, the spinning flow rate is 0.2 to 0.8 mL / h, the ambient temperature is 20 to 30℃, and the relative humidity is 35% to 50%.
Citation Information
Patent Citations
Novel active antibacterial food packaging material and preparation method thereof
CN112679967A
Radiation refrigeration film, preparation method and application in logistics preservation of fruits and vegetables
CN119798893A